Analytic and Numerical Solutions of Couette Flow Problem: A Comparative Study - Thapa, Dhak Bahadur; Uprety, Kedar Nath (Journal of the Institute of Engineering, 2017)
In this work, an incompressible viscous Couette flow is derived by simplifying the Navier-Stokes equations and the resulting one dimensional linear parabolic partial differential equation is solved numerically employing a second order finit difference Crank-Nicolson scheme. The numerical solution and the exact solution are presented graphically. Journal of the Institute of Engineering, 2016, 12(1): 105-113